Clinically Applicable Self-Healing Dental Resin Composites. Issue 8 (2016) - Huyang, George; Sun, Jirun
ABSTRACT: Self-healing is one of the most desired material properties. Herein, we present the design and development of a new self-healing dental composite (SHDC) that can heal micro-cracks autonomously. The SHDC has two functional components in addition to contemporary dental composites: healing powder (HP) and healing liquid (HL) encapsulated in silica microcapsules. The autonomous healing is triggered by micro-cracks which fracture microcapsules in their propagation path and release the HL. As a consequence, the released HL dissolves and reacts with the HP, and then fill the micro-cracks with a cement-like new material. This 3-step crack-release-heal process prevents micro-cracks from causing restoration failure, thus improving the service life of dental restorative material. The mechanical performance of the SHDC prepared were evaluated in terms of elastic modulus and fracture toughness, which were in the upper level compared to commercial dental restorative materials, and the self-healing capability was confirmed through fracture toughness recovery test. In addition, the SHDCs were made with clinically-tested, biocompatible materials, which makes them readily applicable as medical devices.